Can artificial diets be a feasible alternative for the gonadal growth and maturation of the sea urchin Paracentrotus lividus (Lamarck, 1816)?. Issue 2 (23rd October 2019) - Santos, Pedro M.; Ferreira, Susana M. F.; Albano, Pedro; Raposo, Andreia; Costa, José L.; Pombo, Ana
Abstract: Paracentrotus lividus (Lamarck 1816) has high‐value reddish‐orange gonads that are regarded as a delicacy. In this study, three jellified diets have been tested for 90 days to assess the effect of different diets on P. lividus somatic and gonadal growth, gonad color, and reproductive state. All diets contained agar as a gelling agent and consisted of: maize and spinach (A); maize, spinach, and macroalga Laminaria digitata (B); and maize, spinach, and pumpkin Cucurbita maxima (C). Diet B was the most successful in promoting somatic growth with regard to test diameter (1.2 mm month −1 ) and total wet weight (79.9 mg ind −1 day −1 ). The individuals from Diet A presented a higher final gonadosomatic index (9.07 ± 2.39%) where all sea urchins initially presented with an index of 3.33 ± 0.02%. Diets A and C led to a marked advance ( p < .05) in the gametogenic cycle (66.7% and 46.7% of the individuals with mature gametes, respectively), while Diet B resulted in less‐developed gonadal stages, which are more appropriate for commercial purposes in terms of sensorial characteristics appreciated by the consumers. The gonad color analyses confirmed a redder roe in females and also the suitability of C. maxima as a potential gonad color enhancer for P. lividus .